Contribuição à avaliação do nível de serviço de vias considerando emissão de poluentes e tempo de produção - Anselmo Neto, Leandro (2010)
This paper aims to propose a methodology for assessing the level of service of urban roads, in a complementary manner to the method of Classification of the Manual of the routes Capacity - HCM, multitracks with the addition of two variables: the emission of pollutants and cost of lost production time. Initially, it is made a literature review on time loss, pollution generated by traffic and demand management. Then, we talk about the importance of track analysis and performance measures important to keep a track with an acceptable standard of fluidity, and also about the procedure for capacity analysis and the calculation of the level of service, using the HCM. Considering the importance of preserving the environment and the time value to society in the modern world, we propose a complementary part valuing the added variables, subjected to statistical methods, which may involve a background variable service level, ie, a reclassification that is an innovation of the proposed methodology. From the data collected in the field of public and private institutions, it was rehearsed this methodology for one of the most important accesses to the city of Victoria which is the Darcy Castelo de Mendonça Bridge (3ª Bridge) that links up Vitoria and Vila Velha and with compromised planned capacity and high cost of lost production time. After the analysis of the results generated in the test, corroborating with HCM, we inferred that there is loss of production time in two stages - D, E. Thus, it was decided to calculate the cost and not consider it statistically to reclassify the service level. The emission of pollutants - CO - was observed to be relevant at all levels - A, B, C, D, E, and it was applied multivaried statistical techniques to proceed the reclassification of 19% of the level calculated and judged as impaired. It is worth pointing out that the proposed methodology can be applied to any urban road.